2018
DOI: 10.1590/1981-52712015v42n4rb20180056
|View full text |Cite
|
Sign up to set email alerts
|

Ações para a Retomada do Ensino da Humanização nas Escolas de Medicina

Abstract: RESUMO Este artigo é baseado na dissertação do curso de Mestrado Profissional em Ensino em Saúde realizado pelo primeiro autor na Universidade José do Rosário Vellano – Unifenas e cujo título é “Ações para a retomada do ensino da humanização nas escolas de Medicina: uma revisão sistemática da literatura, 2010-2016”. O artigo apresenta os resultados da pesquisa, que efetuou uma revisão sistemática da literatura sobre a retomada da humanização nas escolas de Medicina. A desumanização da medicina tem sido atribuí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
4
0
4
Order By: Relevance
“…According to Mairot et al 16 , humanities based on the literature, cinema, music, opera, narratives and other modalities, by allowing a constructive encounter with values, experiences and diversities, become an instrument of learning and personal growth. Dell Amore Filho et al 15 , when reviewing the teaching of humanization in medical schools, observed that there is an expectation that medical students have humanistic personal characteristics and that they will be able to apply them in the future in professional practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Mairot et al 16 , humanities based on the literature, cinema, music, opera, narratives and other modalities, by allowing a constructive encounter with values, experiences and diversities, become an instrument of learning and personal growth. Dell Amore Filho et al 15 , when reviewing the teaching of humanization in medical schools, observed that there is an expectation that medical students have humanistic personal characteristics and that they will be able to apply them in the future in professional practice.…”
Section: Discussionmentioning
confidence: 99%
“…Ousager and Johannessen point out that there are medical schools that include the humanities in their curricula, but it is difficult to analyze, with any degree of certainty, how much this inclusion effectively trains better physicians 14 . Other authors claim that the results of these mitigating measures lack a more objective analysis 15 and that the absence of instruments able to assess the effectiveness of the humanities as an educational strategy makes it difficult to prove them 16 .…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, o eixo ordenador da formação médica são as Diretrizes Curriculares Nacionais (DCN) para o curso médico, na versão atualizada em 2014, que reforçam a formação humanista e a atuação pautada em princípios éticos, com responsabilidade social 3 A literatura aponta o descompasso entre o idealismo inicial dos estudantes de Medicina e o progressivo sentimento de quase cinismo e falta de comprometimento com os pacientes, que são reduzidos a números ou "casos interessantes" a serem discutidos e abordados [6][7][8] . Exposição ao sofrimento, sensação de impotência no cuidar e alteração das expectativas durante o processo de formação resultam em redução da empatia e contribuem para a desumanização da assistência 9 .…”
Section: Medicina é Ciência E Arteunclassified
“…A abordagem da relação médico-paciente no curso pesquisado acontece em três disciplinas do eixo de desenvolvimento pessoal, durante o ciclo básico, sendo posteriormente orientada pela conduta dos professores das demais disciplinas, levando-os a diversas posturas 26 . Geralmente, espera-se que eles possuam em sua experiência pessoal comportamentos e atitudes que os predisponham à humanização e que sejam aplicados na vida de estudante e do profissional 16,17,27 .…”
Section: Acho Que O Curso Devia Preparar Melhor Profissionalmente Parunclassified